H2 and N2 Remote Plasma Processing of Wurtzite‐Like Oxides: Implications for Energy Applications. Issue 1 (9th December 2015) - Giangregorio, Maria M.; Bianco, Giuseppe V.; Capezzuto, Pio; Bruno, Giovanni; Losurdo, Maria
Abstract : Remote plasma processing is one of the most effective methods for the manipulation of intrinsic defects, doping, stoichiometry, and morphology of a large variety of oxides. Here, we discuss the interaction of polar ZnO and of LiGaO2 and LiAlO2 with atomic hydrogen and nitrogen produced by remote H2 and N2 plasmas. We show that the various crystallographic faces of those wurtzite‐like oxides are characterized by a different reactivity to hydrogen and nitrogen. Specifically, we demonstrate that the O‐polar ZnO is the most stable surface to hydrogen and, therefore, it should be the one of interest to preserve electrode stability in all those applications involving hydrogen. Conversely, we found that H2 remote plasma processing does not significantly alter Li‐based oxides LiGaO2 and LiAlO2, while their nitridation can be exploited to alter the Li composition and mobility. Abstract : H2 and N2 remote plasma processing of a large variety of oxides is a valuable way to tailor their surface properties and make them suitable for energy applications. Among the various oxides, we focus on ZnO, LiGaO2, and LiAlO2 . We demonstrate that among all ZnO faces, the O‐polar is the one suitable for hydrogen related applications. Remote plasma nitridation of LGO and LiAlO is used to tailor Li‐mobility.